MONETARY IDENTIFICATION OF A PERSON AS A PRODUCT OF DISSEMINATION OF VALUES OF WESTERN CIVILIZATION - Тетяна БЕЗПРОЗВАННА (Cхід, 2021)
The article is devoted to the problem of monetary identity, which needs a detailed study in the context of the transformation processes of the modern world. The relevance of the study is that the identity of modern man is becoming unsteady. In seeking guidance for constructing one’s own “Self”, a person finds himself at a crossroads. They lose the identity they had from birth as members of traditional society and are forced to build it independently. The article reveals the preconditions for the emergence of an identity crisis in the context of the development of capitalism and the formation of the economic man. The purpose of the article is to determine the peculiarities of the formation of monetary identity, which has become essentially a by-product of the spread of Western values. To achieve this goal, a structural-functional analysis of social interactions of the subjects of identification has been conducted, as well as general scientific methods of synthesis and generalization of materials, analysis, comparison, deductive and inductive methods, etc. have been used. The main features of monetary identity are that a person begins to be guided by one’s own selfish principles, and money becomes the main value for such a person, appearing as a universal value that is equivalent to all other material values. In the modern world, monetary identity appears as a global and unstable one, it is formed artificially and serves the modern market for profit within the consumer society. It is concluded that in the modern world, money not only serves to improve the objective circumstances of life, but also becomes a means of achieving public recognition. The problem of monetary identity is especially relevant for Ukraine as a country that focuses on the Western type of management with its achievements, values and at the same time problems, and therefore requires further research.